Effect of heavy strength training on thigh muscle cross-sectional area, performance determinants, and performance in well-trained cyclists - Ronnestad, B. R.; Hansen, E. A.; Raastad, T. (European Journal of Applied Physiology, 2010)
The purpose of this study was to investigate the effect of heavy strength training on thigh muscle cross-sectional area (CSA), determinants of cycling performance, and cycling performance in well-trained cyclists. Twenty well-trained cyclists were assigned to either usual endurance training combined with heavy strength training or to usual endurance training only . The strength training performed by E + S consisted of four lower body exercises [3 × 4-10 repetition maximum (RM)], which were performed twice a week for 12 weeks. Thigh muscle CSA, maximal force in isometric half squat, power output in 30 s Wingate test, maximal oxygen consumption (VO2max), power output at 2 mmol l-1 blood lactate concentration ([la-]), and performance, as mean power production, in a 40-min all-out trial were measured before and after the intervention. E + S increased thigh muscle CSA, maximal isometric force, and peak power in the Wingate test more than E. Power output at 2 mmol l-1 [la-] and mean power output in the 40-min all-out trial were improved in E + S (P < 0.05). For E, only performance in the 40-min all-out trial tended to improve (P = 0.057). The two groups showed similar increases in VO2max (P < 0.05). In conclusion, adding strength training to usual endurance training improved determinants of cycling performance as well as performance in well-trained cyclists. Of particular note is that the added strength training increased thigh muscle CSA without causing an increase in body mass.